PEMBINAAN KOMPETENSI PROFESIONAL, PEDAGOGIS DAN KONTEKSTUAL INSTITUSI GURU SD BINAAN DALAM MENERAPKAN DEEP LEARNING - Eko Kuntarto; Asih Nur Ismiatun; Issaura Sherly Pamela; Akhmad Faisal Hidayat (STKIP Persada Khatulistiwa Sintang, 2025)
ABSTRACTTransforming education through innovative implementation of a deep learning approach in the learning process requires qualified teachers and institutional support. Professional competence, teacher pedagogical competence, and institutional contextualization are the fundamental foundations for successful implementation of deep learning. However, in reality, teachers in assisted schools do not yet fully understand and have the skills to integrate the DL approach into their learning practices, and training facilities are still limited. The purpose of this training was to provide guidance on the professional, pedagogical, and institutional contextualization of assisted elementary school teachers in implementing deep learning. The results showed that teacher competence increased, both in terms of understanding and integration in the preparation of lesson plans (RPPP)/student activity worksheet (LKPD) and their application in the learning process. The institution also provided optimal support through the availability of training, comfortable and conducive learning spaces, and facilities for integrating technology. The coaching activities successfully had a positive impact on teachers and schools in implementing deep learning.).Keywords: Professional Competency, Pedagogic Competency, Contextual Competency, Deep Learning Approach, Elementary Teachers ABSTRAKTransformasi pendidikan melalui inovasi penerapan pendekatan deep learning pada proses pembelajaran membutuhkan peran guru yang berkualitas dan dukungan lembaga. Kompetensi profesional, kompetensi pedagogik guru dan kontekstual intitusi menjadi dasar fundamental yang mendukung keberhasilan implementasi deep learning tersebut. Namun, realitanya guru-guru di sekolah binaan yang belum sepenuhnya memiliki pemahaman dan keterampilan dalam mengintegrasikan pendekatan DL tersebut ke dalam praktik pembelajaran, serta masih terbatasnya fasilitas pelatihan. Tujuan dari pelatihan ini adalah untuk melaksanakan pembinaan kompetensi profesional, pedagogik dan kontekstual institusi pada guru SD binaan dalam menerapkan deep learning. Hasil kegiatan menghasilkan bahwa kompetensi guru mengalami peningkatan baik dari level pemahaman dan integrase pada penyusunan RPP/ LKP serta apliksinya pada proses pembelajaran. Institusi juga memberikan dukungan optimal melalui ketersediaan pelatihan, ruang belajar yang nyaman dan konusif, dan fasilitas untuk mengintegrasikan teknologi. Kegiatan pembinaan berhasil memberikan dampak positif pada guru dan sekolah dalam penerapan deep learning.Kata Kunci: Kompetensi Profesioanal, Kompetensi Pedagogik, Kompetensi Kontekstual Insttusi, Deep Learning, Guru Sekolah Dasar